2007
DOI: 10.1007/s00267-007-9036-8
|View full text |Cite
|
Sign up to set email alerts
|

Blowing Smoke in Yellowstone: Air Quality Impacts of Oversnow Motorized Recreation in the Park

Abstract: Snowmobile use in Yellowstone National Park has been shown to impact air quality, with implications for the safety and welfare of Park staff and other Park resource values. Localized impacts have been documented at several high-use sites in the Park, but the broader spatial variability of snowmobile emissions and air quality was not understood. Measurements of 87 volatile organic compounds (VOCs) were made for ambient air sampled across the Park and West Yellowstone, Montana, during 2 days of the 2002-2003 win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Scholarly work in the area of sport and environmental management has been rather scarce and mostly focused on outdoor recreational sports and their impact on the ecosystem (Font et al , 2001; McMillan et al , 2003; Muller et al , 2004; Shively et al , 2008). The literature on professional sport and the environment is even scarcer.…”
Section: Methodsmentioning
confidence: 99%
“…Scholarly work in the area of sport and environmental management has been rather scarce and mostly focused on outdoor recreational sports and their impact on the ecosystem (Font et al , 2001; McMillan et al , 2003; Muller et al , 2004; Shively et al , 2008). The literature on professional sport and the environment is even scarcer.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical mixing in the boundary layer probably did not begin until about noon because of the extremely strong inversion at surface. On the basis of the vertical profiles of potential temperature (not shown), the mixed layer thickness was 100 m (06:00) and 250 m (13:00) on February 12, 2003 and 88 m (6:00), 720 m (13:00), and 995 m (16:00) on Feburary 15, 2003 . This variability suggests that mixing and dilution took place with relatively clean free tropospheric air from aloft mixing down into the boundary layer.…”
Section: Resultsmentioning
confidence: 99%
“…Very little information exists concerning the spatial variation of air toxics from snowmobile emissions in YNP. In this study (also discussed in ref ), we use atmospheric measurements to characterize the spatial variation of air toxics associated with oversnow vehicular traffic. The emission rates of benzene, toluene, ethylbenzene, xylenes, and n -hexane from snowmobile use in the park are estimated on the basis of field measurements conducted in February 2002 and 2003.…”
Section: Introductionmentioning
confidence: 99%
“…2 with up to 15 % MTBE (methyl tertbutyl ether); Jøran Storø, LNS Spitsbergen, personal communication, 2020) with an addition of synthetic oil (about 2 L per 100 km) for two-stroke engines. Snowmobile emissions constitute a significant source of carbon monoxide, nitrogen oxides (NO x ), particles, aldehydes, and a large number of aromatic hydrocarbons (Sive et al, 2003;Bishop et al, 2001;Shively et al, 2008;Zhou et al, 2010;GYC, 2011); further, several studies have confirmed significant contamination of snow along a snowmobile track by PAHs (Mc-Daniel and Zielinska, 2014;Rhea et al, 2005;Oanh et al, 2019). Due to potentially hazardous consequences related to the emissions, the use of snowmobiles is regulated and controlled in the USA with the summed hydrocarbons and carbon monoxide emission limits of 15 and 90 g kW h −1 , respectively (U.S. NPS, 2015).…”
Section: Winter and Spring Cold P1-p3 Periodsmentioning
confidence: 99%
“…No scientific studies on PAC emissions from snowmobiles have been reported yet. Nonetheless, snowmobile driving is a well-documented major source of a list of aromatic hydrocarbons (Zhou et al, 2010;Reimann et al, 2009;Eriksson et al, 2003;Shively et al, 2008), and PAHs were detected in snow along snowmobile tracks (McDaniel and Zielinska, 2014;Rhea et al, 2005;Oanh et al, 2019). Moreover, a factor of 3 higher NO x emissions from snowmobiles compared to gasolinedriven cars in Svalbard are reported by the Norwegian Climate and Pollution Agency (Vestreng et al, 2009) with the main contribution from four-stroke snowmobiles.…”
Section: Nitro-pah Profilesmentioning
confidence: 99%